La relación entre la planificación del gasto y la ejecución del presupuesto en la Universidad Nacional de la Amazonía Peruana, periodo 2022 - Ocampo Meléndez, Geraldine Miluska (2023)
The National University of the Peruvian Amazon makes purchases through the logistics area to meet demand and serve students well, so this office is fundamentally necessary, depending on the programming unit, the selection process, the hiring it is well articulated with the central warehouse and works well; Currently, the logistics of the supply system includes units such as programming, purchases, selection process and central warehouse, every purchase starts from a need, that is why it is important to refer to a programming unit, a part of the demand that reveals the merchandise and/or the minimum details of the service. In this sense, the objective of the research was to determine the relationship between the budget execution and the spending planning of the UNAP, during the period 2022, for which an investigation of a quantitative nature and of a non-experimental type and of a correlational design was conducted. Through a correlation model, it was found that there is a relationship between budget execution and UNAP spending planning, during the 2022 period, this reaction is positive and large, specifically it is 87%. And in addition, the planning of the expenses of the institution has a co-movement with the budget execution and therefore they are important as management tools since they allow us to plan, organize, order, and clarify all the financial obligations of the institution during the period. of exercise.